Textbook of uncommon cancer - Raghavan, Derek (Hoboken, N.J. : Wiley-Blackwell, 2012)
"Now in its Fourth Edition, this text is designed to help clinicians manage the treatment of uncommon cancers, for which, in many instances, there are few established guidelines for care. No longer does each new presentation of an uncommon cancer require extended periods of research. This unique book provides balanced, authoritative, and now, wherever possible, evidence-based guidance on how to address each malignancy. This Fourth Edition is thoroughly revised with new material as well as a new focus on evidence-based research and clinical practice throughout. Clinicians will find guidelines for dealing with management issues, gain insight into real-world clinical decision-making, and save themselves hours of painstaking research through the use of this widely acclaimed, comprehensive guide. A self-contained guide for practicing oncologists who treat patients with rare or infrequently encountered malignancies. It is also an important resource for hematologists and other specialists who deal with malignancies in a particular organ system"--
Uncommon tumors of the kidney -- Uncommon cancers of the bladder -- Urethral cancer -- Uncommon cancers of the prostate -- Rare tumors of the testis and paratesticular tissues -- Uncommon tumors of the oral cavity and adjacent structures -- Rare tumors of the larynx -- Nasopharyngeal carcinoma in nonendemic populations -- Esthesioneuroblastoma -- Adrenal neoplasms -- Uncommon cancers of the thyroid -- Parathyroid carcinoma -- Metaplastic breast carcinoma -- Adenoid cystic carcinoma of the breast -- Non-Hodgkin lymphoma of the breast -- Male breast cancer -- Phyllodes tumor of the breast -- Carcinosarcoma of the breast -- Tubular carcinoma -- Thymoma and thymic carcinoma -- Primary sarcomas of the lung -- Mesotheliomas -- Primary melanoma of the lung -- Large cell neuroendocrine carcinoma -- Bronchioloalveolar carcinoma of the lung -- Primary adenoid cystic carcinoma of the lung -- Uncommon tumors of the esophagus -- Uncommon cancers of the stomach -- Unusual cancers of the pancreas -- Uncommon hepatobiliary tumors -- Cancers of the small bowel -- Unusual tumors of the colon, rectum, and anus -- Gastrointestinal stromal tumors -- Extraovarian primary peritoneal carcinomas -- Borderline tumors and other rare epithelial tumors of the ovary -- Stromal tumors of the ovary -- Germ cell tumors of the ovary -- Fallopian tube cancer -- Nonendometrioid endometrial carcinomas and uterine sarcomas -- Tumors of the cervix -- Tumors of the vulva and vagina -- Rare acute leukemias -- Unusual myelodysplastic syndromes and myeloproliferative neoplasms -- Rare B cell lymphoproliferative disorders -- Uncommon presentations of plasma cell dyscrasias -- Rare bone marrow failure conditions -- Myeloproliferative neoplasms: chronic myelogenous leukemia, polycythemia vera, essential thrombocythemia, and primary myelofibrosis -- Rare T cell lymphomas -- Unusual cutaneous malignancies -- Dermatofibrosarcoma protuberans -- Unusual melanomas -- Primary melanotic tumors of the central nervous system -- Langerhans cell histiocytosis of the central nervous system -- Chordomas -- Atypical and malignant meningiomas -- Primary central nervous system lymphoma -- Choroid plexus papilloma and carcinoma -- Glioma and other neuroepithelial neoplasms -- Medulloblastoma in adults -- Pineal parenchymal tumors -- Craniopharyngiomas -- Ophthalmic cancers -- Introduction to rare cancers of childhood -- Uncommon tumors of the gastrointestinal tract in children -- are pediatric malignancies of the head and neck -- Uncommon pediatric tumors of the thorax -- Uncommon adrenal tumors in children and adolescents -- Uncommon pediatric genitourinary tumors -- Uncommon pediatric brain tumors -- Malignant tumors of the skin and subcutaneous tissue in children.
Includes bibliographical references and index.
Print version record.
Keywords: Cancer; Neoplasms; Rare Diseases; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Cancer; Electronic books